The effectiveness of content mastery services with Jigsaw Type Cooperative Learning Models to improve students' interpersonal communication skills - Andika Fawri; Yarmis Syukur (Universitas Negeri Padang, 2022)
This study aims to describe the effectiveness of the jigsaw cooperative learning model content mastery service to improve students' interpersonal communication skills. This research design uses a quasi-experimental quantitative approach with the non-equivalent control group design. This type of sampling uses non-random sampling, with the sampling technique using purposive sampling. The sample in this study was 64 students who were divided into two classes who had interpersonal communication skills in the low category. Statistical analysis of the data used in this study is non-parametric statistics. This research instrument uses a questionnaire with a Likert scale data analysis technique that has met the requirements of the research instrument, then the data is analyzed using the Wilcoxon Signed Rank Test and Kolmogorov Smirnov 2 Independent Samples. The results showed that: 1) There were significant differences in the interpersonal communication skills of the experimental group students, before (pretest) and after (posttest) following the content mastery service with the jigsaw type cooperative learning model. The findings of this study, firstly, there is a significant difference in the interpersonal communication skills of experimental group students before and after participating in content mastery services with the jigsaw type cooperative learning model with a probability number below alpha 0.05 (0.000 <0.05). Second, there are differences in interpersonal communication skills of control group students before and after participating in content mastery services with probability numbers below alpha 0.05 (0.000 <0.05). Third, there are differences in students' interpersonal communication skills between the experimental group students who were given content mastery services with a jigsaw type cooperative learning model and the control group which was only given content mastery services. The experimental group and control group students' interpersonal communication skills were 0.000, or the probability was below 0.05 (0.000 < 0.05.